Introduction to the issue of state sovereignty and humanitarian action. (22nd July 2013) - Kahn, Clea; Cunningham, Andrew
Abstract : There has been greater discussion among humanitarians in recent years about the rise in the number of 'strong states', and the suggestion has been made that states are increasingly reasserting their sovereignty. This introduction to this special issue of Disasters on 'State Sovereignty and Humanitarian Action' contends that it is not states that have changed, but rather the international framework that surrounds humanitarian action. The latter has altered so substantially that a fundamental gap has developed between states and international humanitarian actors in terms of describing what sovereignty entails and how it is expressed. At the heart of this dilemma are the urgent needs of people caught up in crises, whose well‐being becomes the contested ground on which states and humanitarian actors clash. This paper explores the current and historical dimensions of these shifts, and provides a conceptual overview for this special issue.